The Convergence Dynamics of a Transition Economy : The Case of the Czech Republic - Bruha, Jan (IMF Working Papers; Working Paper ;, 2007)
In this paper we develop a two-country dynamic general equilibrium model by means of which we seek to explain the long-run paths of a converging emerging market economy. We borrow a paradigm from the New Open Economy Macroeconomics literature and amend it to address specific features such as initial asymmetry in development and size of economies as well as different speed of capital accumulation. Using a calibration of productivity and deep parameters for the Czech economy we demonstrate the ability of the model to consistently replicate dynamics in key macroeconomic variables that are essential inputs for commonly used "gap models" in monetary policy routine. Based on the calibration we draw implications for future convergence of the Czech economy.